Pengaruh Penggunaan Multimedia Interaktif Berbasis Augmented Reality Terhadap Kemampuan Pemecahan Masalah Pada Materi Kenampakan Alam Kelas IV Sekolah Dasar - Fani Widia Putri; Tin Rustini; Yusuf Tri Herlambang (Universitas Hamzanwadi, 2025)
Problem solving plays a very important role in the learning and solving process, because later students will gain experience using the knowledge and skills they already have to apply in the process of problem solving activities that are not routine in nature. However, in reality students found difficulties in problem solving abilities in natural appearance material. Thus, the ability to solve problems with natural appearance material in the learning process in the classroom requires interactive media. This research aims to find the effect of using interactive media based on augmented reality on problem solving abilities in natural appearance material in class IV elementary schools. The method used in this research is quantitative with a Quasi Experimental type of research with the aim that the experimental group and control group are not chosen randomly. The samples used were students in class IV of elementary school Neglasari 01 and class IV of elementary school Cinunuk 03. The results of the research showed that there was an influence of the use of interactive media based on augmented reality on problem solving abilities in natural appearance material in class IV of elementary schools. Based on the results of data processing, the average pretest result in the experimental class was (18,20), while the posttest result in the experimental class was (21,88). There was a significant increase in the average pretest and posttest scores. The average pretest score for the control class was (15,88), while the posttest result for the control class was (19,96). The intervention or treatment given in the experimental class has a more significant impact on increasing students' grades.